Biparental care of the Australian Wood Chenonetta jubata - Kingsford, R T (Wildfowl, 1990)
Australian Wood Ducks are unusual among ducks in having extended biparental care. Males and females were equally likely to lead ducklings away from danger or to attack conspecifics or potential avian predators. Pairs that were laying, incubating or attending young, performed more Extreme head up behaviour than other paired birds. In family groups, differences in vigilant behaviour existed between the sexes. Males performed more Extreme head up and stood on higher ground more than females, who stayed closer to the brood. Male Extreme head up was highest when females were laying or incubating and declined with age of the ducklings. In contrast, female vigilance was lowest during laying and incubation, and increased with duckling age. During laying, incubation and early brood care, much of female activity away from the nest site was grazing. Females probably grazed intensely during brood care to recover energy lost during incubation and laying. As small grazing birds, the risks of predation are probably high. To overcome this, males attend the brood, which probably increases duckling survival.